Economic and Resource Potential of the «Lublin Triangle» and Prospects of Activity in the Transport and Logistics Sector - Chebotarov, V.; Ruban, M.; Chebotarov, Ie. (Економічний вісник Донбасу, 2022)
The set of security, institutional, economic, scientific-technical, and natural-technological challenges that have arisen before Ukraine as a result of the full-scale Russian-Ukrainian war necessitates, in particular, the need to substantiate breakthrough measures regarding the country's subject participation in the system of the international division of labor in the conditions of post-war development. One of these particularly effective measures can be the stimulation of the transformation of the «Lublin triangle» alliance, founded by Poland, Lithuania, and Ukraine, into a multilateral international integration organization (with the possible subsequent addition to the alliance of certain countries of the Central and Eastern European subregion; primarily Slovakia, Latvia and Estonia). The article provides a generalized analysis of the economic and resource potential of the «Lublin triangle» in the context of the correlation of its main macroeconomic indicators with the corresponding indicators of the European Union. The priority areas of cooperation of the founding countries of the «Lublin Triangle» are determined according to the sector. The proposal to create a transport-logistics cluster on the basis of the alliance in the composition of the specified six countries as the most effective and promising form of cooperation is justified. The essential features of such a cluster are its «embeddedness» in the pan-European network of transport corridors and transport-logistics hubs, which should cover the «junction-intersections» of passenger and cargo flows on the territory of all participating countries (initial proposals for the geographical location of hubs on the territory of six countries are given). The identification of derived institutional, organizational-economic, and technical-technological parameters of such a transport-logistics cluster is supplemented by a proposal regarding the expediency of working out the measures for its creation to be carried out in the context of the development and implementation of the «Marshall Plan for Ukraine». Сукупність безпекових, інституціональних, економічних, науково-технічних і природничо-технологічних викликів, які повстали перед Україною внаслідок повномасштабної російсько-української війни, зумовлюють, зокрема, необхідність обґрунтування проривних заходів щодо суб’єктної участі країни в системі міжнародного поділу праці в умовах повоєнного розвитку. Одним з таких особливо ефективних заходів може стати стимулювання трансформації альянсу «Люблінський трикутник», заснованого Польщею, Литвою та Україною, в багатосторонню міжнародну інтеграційну організацію (з можливим подальшим доєднанням до альянсу певних країн центрально-східноєвропейського субрегіону; насамперед – Словаччини, Латвії та Естонії). У статті надається узагальнений аналіз економіко-ресурсного потенціалу «Люблінського трикутнику» у контексті співвідношення його основних макроекономічних показників з відповідними показниками Європейського Союзу. За галузевою ознакою визначаються пріоритетні напрями співробітництва країн-засновниць «Люблінського трикутнику». Обґрунтовується пропозиція зі створення на базі альянсу транспортно-логістичного кластеру у складі означених шести країн як найбільш ефективної та перспективної форми співпраці. Сутнісними ознаками подібного кластеру є доцільним закласти його «вмонтованість» в загально-європейську мережу транспортних коридорів і транспортно-логістичні хаби, які мають охопити «вузли-перетини» пасажирських і вантажних потоків на теренах всіх країн-учасниць (наведено вихідні пропозиції щодо географічного розташування хабів на території шести країн). Ідентифікація похідних інституціональних, організаційно-економічних і техніко-технологічних параметрів подібного транспортно-логістичного кластеру доповнюється пропозицією щодо доцільності опрацювання заходів з його створення проводити у контексті розробки та реалізації «Плану Маршалла для України».